The The effect of education level and work experience on employee performance at Capa Resort Maumere - Resing, Maria Tuto; Nasar, Asbi; Milyardo, Boiris; Lasfeto, Deddy B. (Journal of Practical Management Studies, 2024)
The purpose of this study is to determine whether there is an influence of partial level of education on employee performance, the effect of partial work experience on employee performance, and the influence of education level and to determine the effect of work experience simultaneously on employee performance at Capa Resort Maumere. The research design used in this study was quantitative descriptive. The respondents in this study were all employees totaling 29 people. The location where this research was conducted at Capa Resort Maumere. The data collected in this study are data on the level of education, work experience, and employee performance sourced from employees and managers of Capa Resort Maumere. Data collection techniques in this study are questionnaires and document recording, then analysis with preliminary analysis and advanced analysis with quantitative descriptive methods with testing Statistical Package for Social Science (SPSS) version 22 as a tool in processing data. The results of this study show that there is a partial influence of education level on employee performance with a calculated value = 3.722 ≥ Table 2.0555. There is a partial influence of work experience on employee performance with a calculated value = 2,070 ≥ table 2.0555 and a simultaneous influence of education level and work experience on employee performance at Capa Resort Maumere with a significant value for the effect of X1 and X2 simultaneously on Y of 0.000 < 0.05 and a calculated F value of 12,311 > Ftable 2,98.